Analisis Aktivitas Pemasaran Melalui Media Sosial Instagram @cyberacademy.id Pada Pt. Global Inovasi Siber Indonesia Tahun 2023-2024 - Nafrila, Inez; Junipriansa, Donni (eProceedings of Applied Science, 2024)
PT Global Inovasi Siber Indonesia is engagedin the field of Cyber Security which introduces innovativetechnology and innovative strategies to address emerging threats andemerging challenges. Involves reorganizing existing practices andexisting practices and methodologies to adapt to evolving threats and effectively protect digital systems, digitalevolving threats and effectively protect digital systems,networks, and data from cyber threats. PT Global InovasiSiber Indonesia has products namely Bug Bounty Platform,Automated Security Testing Platform, Ransomware Attack,Simulator, Cyber Security Labs, and Hiring Platform. PT GlobalCyber Innovation Indonesia opens a course called CyberAcademy where there are Cyber Security Education andCorporate Training. According to the interview results from informantssuch as the CEO, COO, and digital marketing director show that social media, especially Instagram, plays an important role.that social media, especially Instagram, plays an important role inin building brand awareness and positively impactingcustomer sales. Although sales are not solelyfrom Instagram, the platform still plays a role inattracting prospective students and expanding brand reach.A structured marketing approach, such as the use ofeducational content and targeted promotions, as well as the measurement ofperformance measurement through OKRs (Objectives and Key Results), havehelped the company achieve their goals and continue toexpand their marketing strategy.The purpose of this study is to determinemarketing strategies that are suitable and can increase sales of CyberAcademy and analyze the obstacles that occur inconducting marketing strategies.The result of the research is a marketing strategy through socialInstagram that has been done so far turns out toaffect sales, although there are many platforms from other socialother social media platforms but Instagram can communicate two-way betweenfollowers and the company. The content used nowhas been consistent every week there is some content uploaded.uploaded. Keywords: Marketing Strategy, Marketing, Sales, Social MediaSocial Media, Instagram